2018
DOI: 10.1111/jvim.15240
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, double‐blind, placebo‐controlled pilot study of sacubitril/valsartan (Entresto) in dogs with cardiomegaly secondary to myxomatous mitral valve disease

Abstract: BackgroundThe effects of sacubitril/valsartan (S/V) on the renin‐angiotensin‐aldosterone system (RAAS) in dogs with cardiomegaly secondary to myxomatous mitral valve disease (MMVD) are currently unknown.ObjectivesTo determine the pharmacodynamic effects of S/V on the RAAS, natriuretic peptide concentrations, systolic arterial pressure (SAP), tests of renal function, and serum electrolyte concentrations in dogs with cardiomegaly secondary to MMVD.AnimalsThirteen client‐owned dogs weighing 4‐15 kg with American … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Based on our results, SV at a dose of 20 mg/kg twice a day was chosen for the main study since the changes in SBP and RPP were more consistent when given to these dogs than other groups (i.e., 5 and 10 mg/kg). Interestingly, the dose of SV used in this study was also supported by a recent study in dogs with cardiomegaly secondary to MMVD ( 27 ). SV at a dose of 20 mg/kg orally was also used in a rabbit model of myocardial infarction in which it reduced mean BP at 1–2 h after treatment as well as infarct size ( 28 ).…”
Section: Discussionsupporting
confidence: 77%
“…Based on our results, SV at a dose of 20 mg/kg twice a day was chosen for the main study since the changes in SBP and RPP were more consistent when given to these dogs than other groups (i.e., 5 and 10 mg/kg). Interestingly, the dose of SV used in this study was also supported by a recent study in dogs with cardiomegaly secondary to MMVD ( 27 ). SV at a dose of 20 mg/kg orally was also used in a rabbit model of myocardial infarction in which it reduced mean BP at 1–2 h after treatment as well as infarct size ( 28 ).…”
Section: Discussionsupporting
confidence: 77%
“…In dogs with RAAS activation secondary to sodium restriction, Entresto (sacubitril dosed at 15 mg/kg PO q24h) led to a sustained reduction in circulating aldosterone levels when compared to dogs treated with either placebo or valsartan . This combination has also been evaluated (sacubitril dosed at 20 mg/kg PO q12h) in a small study of dogs with the American College of Veterinary Internal Medicine (ACVIM) stage B2 myxomatous mitral valve disease (MMVD) (Figure ) and was well tolerated during the 30‐day trial . Another novel therapeutic target is the ACE2 enzyme.…”
Section: Suppression Of Raasmentioning
confidence: 99%
“…In dogs with MMVD, the degree of increase in the circulating plasma NE levels is relative to the degree of enlargement of the heart ( 33 , 34 ). Furthermore, several studies on dogs have shown that RAAS activation may be dependent on the severity and duration of cardiac disease ( 33 , 36 , 37 ). These findings potentially account for the relatively slow progression of CKD in dogs with stage B1 MMVD, as observed in our study.…”
Section: Discussionmentioning
confidence: 99%